FAKTOR-FAKTOR MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN SUB SEKTOR BANK DI BURSA EFEK INDONESIA - Dewi Utami; Yennisa Yennisa (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this research is to analyze the effect of profitability, leverage, frim size, and ownership structure on timeliness of financial reporting. The population of this study are all bank companies listed in Indonesia Stock Exchange (IDX) period of 2011-2015 with total 43 companies, and the sample in this study that meets the criteria for the determination of the selected sample 28 companies. Technique of analysis for examining the hipotesis was logistic regression. The results showed that the firm size has positive effect on the timeliness of financial reporting, while profitability, leverage, and ownership structure didn’t have effect on timeliness of financial reporting.Keyword: profitability, leverage, firms size, ownership struture, timeliness